Use of whole-cell bioreporters to assess bioavailability of contaminants in aquatic systems - Zhu, Yi; Elcin, Evrim; Jiang, Mengyuan; Li, Boling; Wang, Hailong; Zhang, Xiaokai; Wang, Zhenyu (Frontiers in Chemistry, 2022)
Water contamination has become increasingly a critical global environmental issue that threatens human and ecosystems’ health. Monitoring and risk assessment of toxic pollutants in water bodies is essential to identifying water pollution treatment needs. Compared with the traditional monitoring approaches, environmental biosensing via whole-cell bioreporters (WCBs) has exhibited excellent capabilities for detecting bioavailability of multiple pollutants by providing a fast, simple, versatile and economical way for environmental risk assessment. The performance of WCBs is determined by its elements of construction, such as host strain, regulatory and reporter genes, as well as experimental conditions. Previously, numerous studies have focused on the design and construction of WCB rather than improving the detection process and commercialization of this technology. For investigators working in the environmental field, WCB can be used to detect pollutants is more important than how they are constructed. This work provides a review of the development of WCBs and a brief introduction to genetic construction strategies and aims to summarize key studies on the application of WCB technology in detection of water contaminants, including organic pollutants and heavy metals. In addition, the current status of commercialization of WCBs is highlighted.